2007
DOI: 10.1099/mic.0.29213-0
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydial SET domain protein functions as a histone methyltransferase

Abstract: SET domain genes have been identified in numbers of bacterial genomes based on similarity to SET domains of eukaryotic histone methyltransferases. Herein, a Chlamydophila pneumoniae SET domain gene was clarified to be coincidently expressed with hctA and hctB genes encoding chlamydial histone H1-like proteins, Hc1 and Hc2, respectively. The SET domain protein (cpnSET) is localized in chlamydial cells and interacts with Hc1 and Hc2 through the C-terminal SET domain. As expected from conservation of catalytic si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 41 publications
1
46
2
Order By: Relevance
“…Evidence for this hypothesis emerged from studies of chlamydial SET proteins. A SET domain protein (cpnSET) from Chlamydophila pneumoniae, which causes acute respiratory diseases in humans, was first shown to methylate the chlamydial histone-like proteins HC1/HC2 (Murata et al 2007). Its homolog nuclear effector (NUE) from Chlamydia trachomatis was subsequently identified as a T3SS effector that enters the nucleus of infected cells, where it associates with chromatin ( Fig.…”
Section: Histone-modifying Bacterial Enzymesmentioning
confidence: 99%
“…Evidence for this hypothesis emerged from studies of chlamydial SET proteins. A SET domain protein (cpnSET) from Chlamydophila pneumoniae, which causes acute respiratory diseases in humans, was first shown to methylate the chlamydial histone-like proteins HC1/HC2 (Murata et al 2007). Its homolog nuclear effector (NUE) from Chlamydia trachomatis was subsequently identified as a T3SS effector that enters the nucleus of infected cells, where it associates with chromatin ( Fig.…”
Section: Histone-modifying Bacterial Enzymesmentioning
confidence: 99%
“…On the other hand, phylogenetic analysis have shown that bacterial SET domain genes have undergone an evolution of their own, unrelated to the evolution of the eukaryotic SET domain genes (Alvarez-Venegas et al, 2007; Murata et al, 2007). This can be substantiated, for example, by performing a BLASTP search at NCBI, with any SET-domain.…”
Section: Bacterial Set Domainmentioning
confidence: 99%
“…An exception are the homologs of the nonhistone-fold protein histone H1 in Chlamydiae [64,119] likely acquired by lateral transfer from a eukaryotic host. HU and its homologs are phylogenetically the most widespread ChAPs in Eubacteria.…”
Section: The Architecture Of Chromatinmentioning
confidence: 99%